Hemicellulosic Polysaccharides From Bamboo Leaves Promoted by Phosphotungstic Acids and Its Attenuation of Oxidative Stress in HepG2 Cells - Xiao, Zhuqian; Li, Jiajie; Wang, Hongpeng; Zhang, Qiang; Ge, Qing; Mao, Jianwei; Sha, Ruyi (Frontiers in Nutrition, 2022)
In this work, we exploited an efficient way to release hemicellulosic polysaccharides (BLHP) from bamboo (Phyllostachys pubescens Mazel) leaves assisted by small amount of phosphotungstic acid. Structural units analysis proved that BLHP-A1 and BLHP-B1 samples possessed abundant low branch chains in →4)-β-D-Xylp-(1→ skeleton mainly consisting of Xylp, Manp, Glcp, Galp and Araf residues. According to the results for antioxidant activity assays in vitro, both of the two fractions demonstrated the potential to scavenge DPPH· and ABTS+ radicals and exhibited relative high reducing ability compared to these of recent reported polysaccharides. In cell level evaluation using HepG2 cells, BLHP-B1 showed more activity for preventing damages from H2O2 in HepG2 cells by improving the enzyme activities of SOD, CAT, GSH-Px and decreasing the production of MDA as well as suppressing reactive oxygen species (ROS) formation. Taken together, our data showed that BLHP could demonstrated its attenuation ability for oxidative stress in HepG2 cells induced by H2O2.